Nutritive Value of Selected Preferred Forage Species by Lactating Camels in the Peri-urban Area of Marsabit Town, Kenya - Sagala, J. I. (Indian Journal of Animal Nutrition, 2020)
The arid and semi-arid lands are the major camel keeping areas in Kenya. However, these areas are largely constrained by year-long shortage of feeds leading to poor performance of grazing camels, particularly during the dry season. Therefore, there is need to determine the nutritive value of the available forage during different seasons in order to conserve the nutritious ones for sustainable peri-urban camel production system. The objective of this study was to assess the chemical composition and digestibility of the most preferred forages by grazing lactating camels in the peri-urban area of Marsabit town. Twenty lactating Somali camels in early stage of lactation (1-4weeks post-partum) and parities 2 and 3 were recruited from large local herds for the study and grouped into 4 groups comprising of 5 camels each based on initial live weight. The camels were allowed to browse in the communal field for 8 hours daily. The most selected forage species were identified through direct observation of 2 browsing camels for 30 minutes each in the morning between 09.00a.m to 10.00 a.m at an interval of 7 days for a total period of 90 days. Using the tallying list of most selected browse species, 20 forage species were sampled in short rains and dry seasons and analysed for proximate composition, detergent fibre and in-vitro dry matter digestibility. The crude protein content of preferred forages during the short rains and dry season ranged from 9.64 to 17.71 % dry matter and 6.87 to 16.81 % dry matter for tree species and 9.73 to 12.19 % dry matter and 8.92 to 10.66 % dry matter for shrubs, respectively. The neutral detergent fibre content during the short rains and dry season was in the range of 24.5 to 48.2% and 21.7 to 42.5% for tree species and, 40.4 to 41.4% and 35.4 to 39.8% for shrubs, respectively. The in-vitro dry matter digestibility during the short rains and dry season was in the range of 35.3 to 74.4% and 33.5 to 66.4% for tree species and, 51.1 to 59.2% and 45.5 to 58.3% for shrubs, respectively. It was concluded that Â Â there were species and seasonal differences in preferences and that the selected species were high in crude protein content and in-vitro dry matter digestibility.